2020
DOI: 10.1002/mgg3.1488
|View full text |Cite
|
Sign up to set email alerts
|

REDBot: Natural language process methods for clinical copy number variation reporting in prenatal and products of conception diagnosis

Abstract: In prenatal diagnosis, chromosomal aberrations, such as aneuploidies and copy number variation (CNV), are one of the important reasons for ultrasound structural abnormalities and products of conceptions (POC). CNVs are pervasive in human genome and account for a large fraction of the population diversity in humans (Girirajan, Campbell, & Eichler, 2011). Many CNVs located in specific genome regions also have clinical significance or have strong associations with well-characterized genomic disorders, such as 22q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…: 607643) on chromosome 17. According to the previous description (Liu et al, 2020 ), these two CNVs were confirmed as disease‐causing, and the two SNVs were classified as variants of unknown significance (VUS) using REDBot according to ACMG guideline.…”
Section: Resultsmentioning
confidence: 99%
“…: 607643) on chromosome 17. According to the previous description (Liu et al, 2020 ), these two CNVs were confirmed as disease‐causing, and the two SNVs were classified as variants of unknown significance (VUS) using REDBot according to ACMG guideline.…”
Section: Resultsmentioning
confidence: 99%